PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP SIKAP ETIS DAN PRESTASI MAHASISWA AKUNTANSI(Studi Pada Perguruan Tinggi Di Kota Pekalongan) - Alvis Muryo Dewanto; Siti Nurhayati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
The purpose of this study is to analyze and determine the effect of EQ and SQ on ethicalattitudes of accounting students, to find out which variables between EQ and SQ are thedominant influence on the ethical attitudes of accounting students, to analyze and find out theinfluence of ethical attitudes of accounting students' achievement. The hypothesis proposed inthis research is Introductory Self significant effect on ethical attitudes of accounting students, Self Control significant effect on accounting students' ethical attitudes, motivationsignificantly influence ethical attitudes of accounting students, Empathy significant effect onaccounting students' ethical attitudes, skills significantly influence ethical attitudes ofaccounting students, Spiritual Intelligence significant effect on ethical attitudes of accountingstudents, Introduction to Self significant effect on student achievement accounting, SelfControl significant effect on accounting students' achievement, achievement motivationsignificantly influence accounting students, Empathy significant effect on studentachievement accounting, Skills significant effect on student achievement accounting,Spiritual Intelligence significant effect on student achievement accounting, Ethical Attitudessignificant effect on student achievement accounting. The model of analysis used is theanalysis of Structural Equation Modelling (SEM) with AMOS Version 4.0. Conclusionsobtained in this study is emotional intelligence and spiritual intelligence does not affect theethical attitudes of accounting students and achievement in Pekalongan. It is known from thevalue of all variables significant effect of emotional intelligence includes self-knowledge,self-control, motivation, empathy and skills as well as spiritual intelligence variables andethical attitudes on the value of significance set at 0.05. The implications of this research isthe process of teaching and learning as a process of development of the human person. Indeveloping a personal means not only the cognitive aspects are growing, but also theemotional aspect. Changes that occur in learners not only due to the learning process but onall aspects relating to him. This should be special attention for STIE Muhammadiyah and Pekalongan Universities, the development of mastery hardskills is very interesting, but thedevelopment of mastery softskills for students to be more enhanced.